Market, Distribution and Marketing Channels for Fertilizers in Karnataka - Ramesh, H. D.; Anand (Indian Journal of Marketing, 2007)
The present study was conducted in the state of Karnataka in the year 2005-06 with the objective to understand the existing fertilizer market, distribution of fertilizers and explore in to the efficiency of marketing channels for fertilizers at the farmers level. A total of 450 farmers and 60 traders including both public and private outlets from 3 districts namely Raichur, Tumkur and Mysore were personally interviewed to fulfill the objectives of the study. Also the available secondary data was extensively used for the study.The results of the study showed that over a period of time, the distribution of fertilizers has been decontrolled and the prices of the fertilizers is going up year after year. Fertilizers Movement Control Order of 1973 brought the distribution of fertilizers under total government control, but after 1991-92 the fertilizers market has undergone phenomenal change with government decisions to slowly phase out the Rs. 5000 cr subsidy given to fertilizers and decontrol it. In April 2003 the government implemented the New Fertilizer policy, which allows Urea manufacturers to market 50 % of the production outside the purview of distribution control. Among the existing marketing channels, the channels having retailer (46.67 % of sample farmers purchased from retailers), cooperatives (32.67 %) and wholesalers (19.11%) as the last market intermediary were very popular channels among the farmers. The analysis showed that the cooperatives channel was the most efficient channel (price efficiency) serving farmers.